The Studying the Components of Social Capital and its Relationship with the Social Happiness in Iranian Students - Foroughinia, zadeh; Mohammadzadeh, Hakimeh; Pourmirza Kalhori, Reza; Kianipour, Neda (International Journal of Engineering and Technology, 2018)
The concept of social capital, due to its nature and content, is associated with almost all the issues in the human, social and health fields. On the other hand, the role of happiness and joy in mental health, physical health, and social inclusion are very important in the field of health. The purpose of this study was to investigate the components of social capital and its relation with social happiness of students in Kermanshah University of Medical Sciences in 2017. This study is descriptive-correlational. The research population consisted of 450 students in Kermanshah University of Medical Sciences in 2017who were selected by cluster sampling. Bullen& Onyx Standard Social Capital Questionnaire and Oxford Happiness Questionnaire (OHQ) were used to collect data. Data were analyzed using descriptive and inferential statistics (Pearson correlation coefficient). Data analysis was performed using SPSS-23 software. In this research, social capital score was 3.17 ± 0.45 according to the students' score and the mean score of the social happiness was 3.68 ± 0.14. There was a positive and significant relationship between two variables of social capital and social happiness of students (r=0.423). Among the social capital fields, the variables of the value of life, trust, and security had the most and the least relationship with the overall social happiness. Social capital and its aspects have a direct and significant relationship with the social happiness; therefore, with increasing the social capital, the level of social happiness increases.